Cold War at 30,000 feet : the Anglo-American fight for aviation supremacy - Engel, Jeffrey A. (Harvard University Press, 2007)
"Jeffrey Engel reveals the "special relationship" between the United States and Great Britain in a new and far more competitive light. As allies, they fought communism. As rivals, they locked horns over which would lead the Cold War fight. In the quest for sovereignty and hegemony, one important key was airpower, which created jobs, forged ties with the developing world, and perhaps most importantly in a nuclear world, ensured military superiority." "Engel traces the bitter fights between these intimate allies from Europe to Latin America to Asia as each sought control over the sale of aircraft and technology throughout the world. The Anglo-American competition for aviation supremacy affected the global balance of power and the fates of developing nations such as India, Pakistan, and China. But without aviation, Engel argues, Britain would never have had the strength to function as a brake upon American power, the way trusted allies should."--Jacket